OPTIMIZATION OF PROJECT DURATION USING CPM METHOD AND MONTE CARLO CRYSTAL BALL SIMULATION - Muhammad Chilmi; Diah Ayu Restuti Wulandari (NAROTAMA UNIVERSITY, Indonesia, 2020)
There are many aspects of uncertainty on the project that affect accuracy in the process of the making project schedule, so it needs analysis of the probability of the scheduling and sensitivity of work that affects to completion total duration of the project. The existing schedule of the project Laves Mall proved was late because ignored the uncertainty aspects, by using monte Carlo crystal ball simulation will help to find completion duration of the project with the most efficiency duration, Existing completion duration project is 500 days started on 6 July 2018 to 1 December 2019, after simulation change into 604 days and the project started same as existing duration which is on 6 July 2018 to 15 March 2020 by the deviation of the duration is 104 days or about 3 months. And the highest sensitivity work activity that affects the entire duration completion of projects is cutting off of head pile cap work with sensitivity percentage is 18,8%.